Implementation of a fuel measurement system based on the gravimetric principle for applications in engine test bench (2018)
This paper documents the implementation process of a fuel measurement system based on the gravimetric principle for applications in Engine Test Bench. To do this, the design of the measurement hardware consists of a gravimetric scale with serial output, feed pump, and a valve; which interact with each other thanks to the programming developed in the Arduino UNO® environment, it is possible to guarantee protection against possible disturbances that may affect the data measured by the scale by means of an acrylic structure. For the visualization and interaction with the information collected by the meter, an executable application is made using the LabView ™ computational tool. Finally, a series of runs are carried out to guarantee compatibility with the existing testbench in the laboratory and to demonstrate the functionality of the system.